Assessment of risk factors associated with HTLV-1/-2 infection among people living with HIV/AIDS in Bauchi State, Nigeria. Issue 1 (1st January 2020) - Babayo, Adamu; Abdullahi, Idris Nasir; Safiyanu, Mansur Bala; Adekola, Hafeez Aderinsayo; Usman, Jamila Nasir
ABSTRACT: Introduction : Human T-cell lymphotropic virus (HTLV) is associated with shorter survival of HIV co-infected persons due to masked immunosuppression. Since both retroviruses share similar routes of transmission, there is a need to determine risk factors associated with these pathogens. This study aimed to assess the risk factors associated with HTLV-1/-2 and HIV co-infected among persons attending a secondary hospital in Ningi, Bauchi State, Nigeria. Methods : Blood samples were collected from 182 HIV infected persons and analysed for anti-HTLV-1/2 IgM and IgG antibodies using commercial Enzyme-Linked Immunosorbent Assay (ELISA) kits. Interviewer-based questionnaire were used to collate sociodemographic and risk factor data of the subjects and clinical history were obtained from participants' medical records. Results : The seroprevalence of anti-HTLV-1/-2 IgM and IgG were 9.9% and 19.8%, respectively. Out of the 80 ART-naïve, 25 (31.3%) were IgM seropositive. Out of 102 ART-experienced, 11 (10.8%) were anti-HTLV-1/-2 IgM positive. There was a significant association between ART status and seroprevalence of anti-HTLV-1/-2 IgM (p=0.009). However, there was no significance association between seroprevalence of HTLV IgM and gender of the subjects (p=0.06). There was a significant association between the seroprevalence of anti-HTLV-1/-2 IgG and education level of subjects (p=0.039). However, no association between anti-HTLV-1/-2 IgG and other sociodemographic variables studied (p˃ 0.05). History of injury from sharp objects (aOR: 5.3, p<0.0001) and consistent protective sexual practice (aOR: 2.27, p=0.033) were associated with seroprevalence of anti-HTLV-1/-2 IgM. Discussion : High seroprevalence of HTLV-1/-2 and HIV co-infection was reported. ART status, protective sexual intercourse and injuries with sharp objects were identified risk factors of co-infection. It's recommended to consider HTLV screening for all HIV infected persons and vice versa.